The Cement Sector in Saudi Arabia between Challenges and Aspirations: An Analytical Study of the Cement Sector During the Period 2000 to 2021 - Aljohani, Ahmed Falah (Journal of Economic, Administrative and Legal Sciences, 2023)
The research aimed to study the cement sector in Saudi Arabia during the period 2000 to 2021. Through the impact of the production of the cement sector on the independent affecting variables. It is the gross fixed capital formation and government expenditure related to the cement sector during the study period. The descriptive method and standard analysis were followed. Independent variables were analyzed to test the two hypotheses related to cement production in Saudi Arabia. The results of the study showed that there is a statistically significant effect on government spending related to the cement sector on cement production in Saudi Arabia. There is a long term negative impact of gross fixed capital formation on cement production and sales. The researcher recommends strengthening government projects, supporting, and promoting cement exports to the region’s markets, and organizing a special tax base for the cement sector, which leads to an improvement in the cement sector.